1976
DOI: 10.1007/bf01095900
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde pancreatography

Abstract: Thirty-five pancreatograms were selected from 62 which were obtained during endoscopic cannulation of the papilla of Vater with retrograde injection of radiopaque medium. Pancreatograms were selected on the basis of the quality of the study and on the absence of any clinically demonstrable pancreatic disease. Measurements were made of the main pancreatic duct (MPD) in the head, body, and tail, as well as the length of the duct. Although there is a wide range of normal, practical reference figures for the diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…It was possible at the first examination in all Beagles. Similar to humans, both branches of the canine accessory pancreatic duct had a decrease in size from proximal to distal but with smaller mean duct diameters 44–46 . In humans, the mean diameter of the normal pancreatic duct is 3.1–3.3 mm in the head, 2.4 in the body and 1.4–1.5 mm in the tail, 45,46 and therefore, more than three times bigger than the mean duct diameter determined in the Beagles of this study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It was possible at the first examination in all Beagles. Similar to humans, both branches of the canine accessory pancreatic duct had a decrease in size from proximal to distal but with smaller mean duct diameters 44–46 . In humans, the mean diameter of the normal pancreatic duct is 3.1–3.3 mm in the head, 2.4 in the body and 1.4–1.5 mm in the tail, 45,46 and therefore, more than three times bigger than the mean duct diameter determined in the Beagles of this study.…”
Section: Discussionmentioning
confidence: 79%
“…The length of the branches of the accessory pancreatic duct in Beagles was shorter than the pancreatic duct in humans 44,45 . However, it is to be expected that larger dog breeds also have longer pancreatic ducts.…”
Section: Discussionmentioning
confidence: 89%
“…Sivak and Sullivan [10]and Ansel [11]reported that the large inferior unpaired branch from the MPD was found in the head of the gland in 55.5% of the examinations. The short-type APD joins the MPD near its first inferior branch and is less likely to possess a long inferior branch from the APD.…”
Section: Discussionmentioning
confidence: 99%
“…ERCP development has contributed much to the diagnosis of biliary and pancreatic diseases and, more importantly, to the study of anatomical morphology and structure which were previously dependent on autopsy and surgery. Normally, the morphology and size of the pancreatic duct and duodenal papilla of each person are different, and accordingly, many diagnostic references have been reported by many researchers on normal pancreatography 3 , 4 , 6 , 7 ) .…”
Section: Discussionmentioning
confidence: 99%